Alterations in the vascular architecture of the dorsal root ganglia in a rat neuropathic pain model - Kubíček, Luboš; Kopáčik, Roman; Klusáková, Ilona; Dubový, Petr (Annals of anatomy, 2010)
An alteration in the structural arrangement of blood vessels identified by RECA immunohistochemistry was studied in a rat L4 dorsal root ganglia (L4-DRG) neuropathic pain model. We compared a three-dimensional (3-D) reconstruction of the vascular architecture surrounding bodies of the primary sensory neurons in the L4-DRG of naïve rats with that of rats that had surgically undergone unilateral sciatic nerve ligature. Rhodamine-conjugated dextran (Fluoro-Ruby) was used for retrograde labelling of neurons, the axons of which had been injured by nerve ligature. In contrast to DRG from naïve rats and contralateral DRG from operated rats, an increased proportion of RECA+ vascular area and the appearance of nest-like arrangements of blood vessels around neuronal bodies with injured axons were observed in L4-DRG ipsilateral to the sciatic nerve ligature. Fractal analysis confirmed a higher degree of vascular branching, irregularity, and tortuosity in L4-DRG related with sciatic nerve injury. The results suggest that nerve injury induces changes in vascular architecture in associated DRG.
Keywords: Animals; funkční lateralita; nervus ischiadicus; Hyperalgesia; cévy; nemoci periferního nervového systému; Rats, Wistar; Sciatic Nerve; Functional Laterality; Peripheral Nervous System Diseases; nervové receptory; neurony; Wallerian Degeneration; Sensory Receptor Cells; hyperalgezie; Neurons; počítačové zpracování obrazu; Ganglia, Spinal; spinální ganglia; krysa rodu Rattus; Wallerova degenerace; Blood Vessels; zvířata; Rats; Image Processing, Computer-Assisted; potkani Wistar